Pengaruh Pengungkapan Lingkungan dan Karbon terhadap Nilai Perusahaan - Setya Permana, Aryo Bimo; Tjahjadi, Bambang (E-Jurnal Akuntansi, 2020)
Transparency of corporate environmental information is needed by stakeholders, especially capital market investors, to assess risk. This study aims to examine the effect of environmental disclosure on firm value. Based on testing using a sample of agricultural and mining sector firms listed on the Indonesia Stock Exchange (IDX), the results indicate that environmental information disclosed by the company is partially useful for decision making. It is because the company's participation in disclosing environmental responsibility activities is still low. This requires the regulator to further increase supervision for the sake of better quality of environmental disclosure. Keywords: Environmental Disclosure; Firm Value; Environmental Cost; Carbon Emission Disclosure.